THE IMPACT OF LEARNING MODEL OF PROBING-PROMPTING TOWARD INDONESIAN STUDENTS’WRITING IN TEXT SPEECH - meliyawati meliyawati (Jurnal Bahastra, 2019)
AbstrakThe aim of the research is to find whether there is any influence of learning model of Probing-Prompting on the ability to write speech texts. The researcher used quantitative research using experimental design. The sample technique used classter random sampling. The results of the lottery performed on the two available were X-B class as the experimental class and IX-A class as the control class. Each class was 22 and 25 students. Based on the test scores of the ability to write a speech script by using a probing prompting learning model for Class IX students. It shows that the average ability is 79.5 with the lowest value of 65 and the highest value of 90, has a median value of 80.2 and mode 81.5. While the ability to write speech scripts by using expository models in other Class. This is shown by the results of hypothesis testing (t test) with a significant level of 0.05, that is 5.00 is greater than t table 2.026, then HO is rejected and HI is accepted. It means that there is a positive influence on the use of probing prompting learning models on the ability to write speech scripts.